Perceptions and experiences of older adults in a youth community health volunteer–led health coaching program in Singapore: A qualitative study - Audrey Shu Ting Kwan; Jasmine Yee Ru Cheng; Jed Jasman; Elliott Weizhi Sim; Alicia Shi Yao Chee; Ka Shing Yow; Jie Xin Lim; Si Qi Lim; Thaddeus Chi En Cheong; Nerice Heng Wen Ngiam; Muhammad Razzan Razaki; Xiaoting Huang; et al. (PLoS ONE, 2025)
Background With an aging global population, there is a growing emphasis on community-based approaches to preventive health for older adults. While Community Health Volunteers have been found to be effective in empowering older adults to manage their chronic conditions, there is limited research on the role of Youth Community Health Volunteers (YCHVs) and little is known about how older adults perceive their role and effectiveness. Objectives This qualitative study explores older adults’ experiences and perceptions of a YCHV-led health coaching program following community health screening in Singapore. Methods We conducted one-to-one semi-structured interviews with 19 older adults who had participated in HealthStart, a YCHV-led health coaching program. Purposive sampling was used to ensure representation across diverse demographic backgrounds and varying levels of program engagement. Interviews were carried out between November 2023 and January 2024 in community centers, healthcare facilities, or via telephone/Zoom, and explored participants’ experiences with the program, perceptions of YCHVs, and health-related outcomes. We analyzed data thematically using deductive and inductive coding. Results We generated five themes: (1) How YCHV facilitation contributed to prevention outcomes, (2) YCHV facilitation techniques, (3) Intrinsic factors influencing older adults’ receptivity towards YCHVs, (4) Older adults’ perceptions of YCHVs, and (5) YCHVs’ potential to be further empowered as health advocates. Findings provided insights into health behaviors of older adults, the perceived role of YCHVs in influencing these behaviors, and potential and opportunities to strengthen YCHVs’ capacity as health advocates. Conclusion Engaging YCHVs as preventive health advocates for older adults appeared both acceptable and promising. This study highlights the potential for YCHV scale-up, while emphasizing the need for targeted training in behavior change and referral to community resources. Beyond individual health gains, such initiatives may help address ageist attitudes, foster intergenerational solidarity, and complement primary care efforts.